1977
DOI: 10.1002/cne.901710303
|View full text |Cite
|
Sign up to set email alerts
|

A Golgi study on the habenular nucleus of the cat

Abstract: The habenular nucleus of kittens was studied using the rapid Golgi and the Golgi-Kopsch silver impregnation methods. The neurons of the medial habenular nucleus (MH) were classified into two types. The type I neurons, the main constituents of the MH, had piriform cell bodies with a mean diameter of 12 mum by 18 mum and two to five primary dendrites; dendrites had many spines. The type II neurons (14 X 23 mum) were fusiform in shape and one to three primary dendrites arose from each pole of the cell bodies; den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
27
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 54 publications
8
27
0
Order By: Relevance
“…Morphological features of the MH ...., -a neurons observed in the present study were similar to those of the MH neurons noted in the lamprey (Heier 1948), frog (Kemali and Braitenberg 1969;Kemali and Lazar 1985) and mouse (RamOn y Cajal), and the type I MH neurons in the cat (Iwahori 1977). As was reported in the mouse and cat, the dendritic field of the MH neurons in the red stingray was occasionally impregnated in an overlapped manner, suggesting the existence of the glomerular structure in the MH.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Morphological features of the MH ...., -a neurons observed in the present study were similar to those of the MH neurons noted in the lamprey (Heier 1948), frog (Kemali and Braitenberg 1969;Kemali and Lazar 1985) and mouse (RamOn y Cajal), and the type I MH neurons in the cat (Iwahori 1977). As was reported in the mouse and cat, the dendritic field of the MH neurons in the red stingray was occasionally impregnated in an overlapped manner, suggesting the existence of the glomerular structure in the MH.…”
Section: Discussionsupporting
confidence: 85%
“…The type I LH neurons in the present study resembled the multipolar neurons seen in the LH of the mustel, mouse and cat. On the other hand, general features of the type II LH neurons in the red stingray were similar to those of the interneurons seen in the cat LH (Iwahori 1977). However, the exact character of the type II LH neurons requires further study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the red stingray, the MH and LH received different SM fibers; this is known to be the case in many other species as well. The terminal patterns of the SM fibers in the MH observed in the present study were similar to those observed in the mouse (RamOn y Cajal 1911) and cat (Iwahori 1977). Convergence of several terminals seen in the present study was also observed in the cat.…”
Section: Discussionsupporting
confidence: 89%
“…In mammals, terminal patterns of the afferent fibers in the HG was studied in detail using the rapid Golgi method (RamOn y Cajal 1911;Iwahori 1977) as well as the experimental methods (Herkenham and Nauta 1977). The afferent fibers to the selachian HG have been studied by numerous investigators (Edinger 1892;Haller 1898;Ariens Kappers 1906;Sterzi 1909;Ariens Kappers and Carpenter 1911;Johnston 1911;Bergquist 1932;Addens 1945;Farner 1978;Smeets, Nieuwenhuys and Roberts 1983).…”
mentioning
confidence: 99%